Wear Behaviours of Sustainable Biolubricants: Influence of Fatty Acid Compositions and Surface Roughness in Mixed Lubrication Regimes - Gasni, Dedison; Haznam Putra; Rio Muhammad Nur (Advance Sustainable Science Engineering and Technology, 2025)
The advantage of biolubricant compared to mineral oil is that biolubricant can ensure environmental sustainability. This research aims to investigate sustainable biolubricants of virgin coconut oil (VCO) and olive oil on wear behaviours with different fatty acid compositions and surface roughnesses in the mixed lubrication regimes. Tests were carried out on pin-on-disc equipment at a speed of 500 rpm with loads of 50 and 100 N. We used two types of biolubricants and surface roughness of the disks (0.8 and 6.3 µm). The research results show that the lauric acid content in VCO could reduce the wear rate of the disk. The surface roughness of the disc had a significant influence on the wear rate for both biolubricants; the smoother the surface of the disc, the more wear rate will decrease. The effect of surface roughness of the disc with both biolubricants could reduce the scar width of the disc and the scar diameter of the pin. The scar width of the disk was higher when compared to the scar diameter of the pin; by using VCO, there was a decrease of percentage in scar width of 32% by using smooth surface. VCO could be a promising sustainable bio-based lubricant in the future, especially in the mixed lubrication regimes